2012
DOI: 10.1080/1067828x.2012.636687
|View full text |Cite
|
Sign up to set email alerts
|

Substance Use and Sexual Orientation among East and Southeast Asian Adolescents in Canada

Abstract: The purpose of this study was to examine the relationship between substance use and sexual orientation among Asian adolescents in Canada. We analyzed an East and Southeast Asian subsample of a province-wide, school-based survey (weighted N = 51,349). Compared to heterosexual adolescents of the same gender, gay, lesbian, bisexual, and mostly heterosexual adolescents were more likely to use alcohol, marijuana, or other illicit drugs. Particularly, sexual minority girls were at increased risk for substance use. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 48 publications
1
9
0
Order By: Relevance
“…When research combines all sexual minorities into one group, important heterogeneity may be masked. While a growing body of research has identifi ed health disparities among youths describing themselves as mostly heterosexual ( Corliss, Austin, Roberts, & Molnar, 2009 ;Homma, Chen, Poon, & Saewyc, 2011 ;Marshal et al, 2009 ), factors contributing to their greater smoking and how they may be similar to or different from other sexual minorities are poorly understood. Mostly heterosexual youth differ from other youth in their behavioral experiences and identity development ( Austin, Conron, Patel, & Freedner, 2007 ;Thompson & Morgan, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…When research combines all sexual minorities into one group, important heterogeneity may be masked. While a growing body of research has identifi ed health disparities among youths describing themselves as mostly heterosexual ( Corliss, Austin, Roberts, & Molnar, 2009 ;Homma, Chen, Poon, & Saewyc, 2011 ;Marshal et al, 2009 ), factors contributing to their greater smoking and how they may be similar to or different from other sexual minorities are poorly understood. Mostly heterosexual youth differ from other youth in their behavioral experiences and identity development ( Austin, Conron, Patel, & Freedner, 2007 ;Thompson & Morgan, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…Though some studies have described risk and protective factors for alcohol-related harms, few have examined high school students, and only one focused on sexual orientation in this population (Homma et al 2012). This study, conducted by Homma et al in 2012(Homma et al 2012, examined the relationship between experiencing at least one alcohol-related harm and sexual orientation among East and Southeast Asian adolescents in British Columbia, Canada. Homma et al (2012) focused on the group of adolescents who identified as Bmostly heterosexual^-one of the most commonly reported sexual identities of young adults (Savin-Williams and Vrangalova 2013).…”
Section: Introductionmentioning
confidence: 99%
“…This study, conducted by Homma et al in 2012(Homma et al 2012, examined the relationship between experiencing at least one alcohol-related harm and sexual orientation among East and Southeast Asian adolescents in British Columbia, Canada. Homma et al (2012) focused on the group of adolescents who identified as Bmostly heterosexual^-one of the most commonly reported sexual identities of young adults (Savin-Williams and Vrangalova 2013). Mostly heterosexual female students were found to be more likely than their heterosexual counterparts to experience any harm from alcohol or drugs (odds ratio (OR) = 2.09; 99% confidence interval (CI) = 1.73-2.52).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…the sample size of asian sexual minority youth in that study was quite small (only 65 adolescents), however, and the researchers suggested the analyses may have been under-powered. in canada, an analysis of asian students within the Bc adolescent health survey found students who identified as lesbian, gay, bisexual, or mostly heterosexual were more likely than their heterosexual peers to use alcohol, cannabis, and other illicit drugs (homma, chen, Poon, & saewyc, 2012).…”
mentioning
confidence: 99%